2017
DOI: 10.1097/md.0000000000007924
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of mortality in bloodstream infections caused by Klebsiella pneumonia

Abstract: The prevalence of Klebsiella pneumonia bloodstream infections (KP-BSIs) is increasing worldwide. Few study reports focus on the KP-BSIs published in Mainland China over the previous years. This study aimed to describe the risk factors of mortality from KP-BSIs.A retrospective study was conducted in a teaching hospital in Shanghai, China, for a period of 4 years. Risk factors related to the patient mortality were analyzed using the binary logistic regression model.Of 104 patients with KP-BSIs, the overall 30-da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 35 publications
1
14
1
1
Order By: Relevance
“…Our single-center, case-control study including 129 patients with K. pneumoniae bacteremia revealed that the 30-day mortality in patients with K. pneumoniae bacteremia was 10.9%, which was lower than that previously reported [2][3][4]. Second, it was suggested that sepsis and iutA are independent predictors of the 30-day mortality of K. pneumoniae bacteremia.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Our single-center, case-control study including 129 patients with K. pneumoniae bacteremia revealed that the 30-day mortality in patients with K. pneumoniae bacteremia was 10.9%, which was lower than that previously reported [2][3][4]. Second, it was suggested that sepsis and iutA are independent predictors of the 30-day mortality of K. pneumoniae bacteremia.…”
Section: Discussioncontrasting
confidence: 56%
“…Particularly, K. pneumoniae bacteremia is a clinically critical presentation associated with high mortality. Previous studies have indicated that mortality was approximately 16%-40% in patients with K. pneumoniae bacteremia [2][3][4]. Therefore, elucidating the predictors associated with mortality in K. pneumoniae bacteremia is critical in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…However, resistance to carbapenems is making the treatment of CR K. pneumoniae extremely difficult. The results of a retrospective study conducted at a Shanghai teaching hospital revealed an overall 30-day mortality rate for BSIs of 25% for patients who had contracted CR K. pneumoniae [31]. Another retrospective cohort study on the effect of appropriate combination therapy on mortality in patients with BSIs caused by carbapenemase-producing Enterobacteriaceae reported that use of combination therapy was associated with improved survival only in patients with a high mortality risk score [32].…”
Section: Discussionmentioning
confidence: 99%
“…Although KP has had an increasingly important role in infection at various sites (i.e., urinary tract, pulmonary, bloodstream, biliary tract) in recent years, there has been little research on CAUTIs caused by KP (9,11,15,16). To our knowledge, this is the first population-based study of KP-CAUTIs in China.…”
Section: Discussionmentioning
confidence: 95%